Hubungan Peran Supervisor dengan Kualitas Pendokumentasian Asuhan Keperawatan sesuai SNARS di RSD Idaman Kota Banjarbaru - Adawiah, Rabiatul; Setiawan, Herry; Rizany, Ichsan (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Documentation as collateral proof of the quality of nursing care provided. Objective to know the role ofsupervisors with the quality of documentation of nursing care according to SNARS at RSD. Design of CROSSSSectional research, 11 team chairmen and 82 implementing nurses with purposive sampling techniques.Research instruments using observation sheets and questionnaires. Data was analyzed using the Fisher Excattest for the team leader and Chi Square test for executive nurses. The results of the team leader's perception ofthe supervisor's role was 54.5%, and the implementing nurse was either 58.5%, the quality of the team's chiefdocumentation was not good 72.7%, and the implementing nurse was 81.7%. The result is no relationship rolesupervisor with the quality of the documentation of nursing care team Chair as per SNARS (p value = 0,182 >0.05), there is no relationship of supervisor role with the quality of the documentation of nursing care nursesaccording to SNARS (p value = 0,458 > 0.05). Not related to the role of supervisors with the quality of thetreatment of nursing care can occur because it is influenced by motivation, knowledge, workload, attitude, time,and intensively.